Frank Ramsey, a shooting star in the mathematical universe: Frank Ramsey, una estrella fugaz en el universo matemático - Arguedas, Vernor (2020)
Various aspects of the short but brilliant life of Frank Ramsey are presented, whose achievements continue to set the path